AGROFORESTRY PRACTICES AND THEIR POTENTIAL CONTRIBUTIONS TO SOIL FERTILITY AND FOOD PRODUCTION IN KATSINA STATE, NIGERIA (2011)
Unsustainable forest land use practices have resulted in land degradation in the northern part of Nigeria leading to low crop yield. Agroforestry is a viable option for reversing dwindling crop yields through proper soil management practices. There is notably no sufficient published information on the contributions of agroforestry to food production in Katsina State. The practices of agroforestry and its potential to slow down the pace of soil degradation and boost food production in Katsina State was therefore investigated. Multistage stratified sampling was used to select respondents for the study. Three Local Government Areas (LGAs) were randomly selected from each of the agro-ecological zones (Sahel, Sudan and Guinea) of Katsina State. Within each of the selected LGAs, one community was randomly selected and forty respondents were randomly sampled from each community. Using structured questionnaire, information was sought on the socio-economic and demographic characteristics of respondents, Agroforestry Practices (AP), attitude to AP, information sources on AP and AP perceived benefits. Chemical characteristics of soil samples from agroforestry and non-agroforestry plots of respondents in the three zones were also determined using standard methods. Data were analysed using descriptive statistics, Chi-square and ANOVA at p = 0.05. Most of the respondents (96.3%) were married, 82.5% were male and 50.0% were between 30 and 49 years of age. Their primary occupation was mostly farming (66.1%) while modal annual farm size was 1 – 2 hectares. Means of land acquisition was more by inheritance (50.8%) and 33.1% of the respondents made an annual income of between N30,000.00 – 40,000.00. The major farm enterprises were food crop production (74.1%), livestock (5.2%), tree crops (0.6%) and various combinations of these (19.0%). Multipurpose trees on farmland (79.2±11.1%), windbreaks (50.0±13.3%), woodlots (49.7±3.9%), improved fallow in shifting cultivation (32.2±26.3%) and home gardens (24.7±6.9%) were the common AP by the respondents. Benefits of AP to the respondents included preservation of the environment (98.5%), provision of fruits and leaves (98.3%), improvement of soil fertility (97.5%), erosion control (97.5%), improvement of farmers income (95.8%) and provision of fodder (92.7%). Also, 93.9% of the respondents reported increased yield of arable crops from a mixed tree and arable crop farm. Majority of the respondents (70.3%) identified scanty rainfall, land shortage and inadequate labour as problems while 12.8%, 4.7% and 4.4% respectively identified each of the problems as limiting AP. Although significant variation was observed in AP in the zones, sources of information significantly impacted adoption of AP in Sahel and Sudan but not in Guinea savanna zone. Significant variation was observed in soil pH, total nitrogen, Mg2+, K+ and Na+ between agro-forestry and non agro-forestry plots with soil nutrient and organic matter content skewing in favour of agroforestry plots. UNIVERSITY OF IBADAN LIBRARY iii Agroforestry practices enrich the soil with important nutrients and prevent soil erosion. The adoption of multipurpose trees on farmland in Katsina state will help in preventing environmental degradation, desertification and enhance food crop production. Keywords: Agroforestry practices, Agro-ecological zones, Farm enterprises, Soil degradation Word Count: 476